2022
DOI: 10.1101/2022.08.03.22278363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is common in post-acute sequelae of SARS-CoV-2 infection (PASC): Results from a post-COVID-19 multidisciplinary clinic

Abstract: Background The global prevalence of PASC is estimated to be present in 0.43 and based on the WHO estimation of 470 million worldwide COVID-19 infections, corresponds to around 200 million people experiencing long COVID symptoms. Despite this, its clinical features are not well defined. Methods We collected retrospective data from 140 patients with PASC in a post-COVID-19 clinic on demographics, risk factors, illness severity (graded as one-mild to five-severe), functional status, and 29 symptoms and princ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…This study confirms prior research showing that a substantial percentage of people who contract COVID-19 develop a condition that meets the criteria for a CCC diagnosis of ME/CFS. This percentage is comparable to earlier studies [ 16 , 17 , 18 , 20 ], except that of González-Hermosillo et al [ 21 ]. It is apparent that many who have been infected with SARS-CoV-2 and have persisting symptoms will meet a ME/CFS case definition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study confirms prior research showing that a substantial percentage of people who contract COVID-19 develop a condition that meets the criteria for a CCC diagnosis of ME/CFS. This percentage is comparable to earlier studies [ 16 , 17 , 18 , 20 ], except that of González-Hermosillo et al [ 21 ]. It is apparent that many who have been infected with SARS-CoV-2 and have persisting symptoms will meet a ME/CFS case definition.…”
Section: Discussionsupporting
confidence: 91%
“…For example, in the study by Jason and Islam [ 16 ] of 359 patients with Long COVID, 49% met ME/CFS criteria. In another study of 140 participants with Long-COVID, Bonilla et al [ 17 ] found that 43% met the criterial for ME/CFS; Twomey, et al [ 18 ] found that 58.7% of those infected with COVID-19 meet ME/CFS criteria. Similarly, Mancini et al [ 19 ] studied patients with unexplained dyspnea among those who had Long COVID for a mean of 8 months and found that 46% met the criteria for ME/CFS.…”
Section: Me/cfs and Post-exertional Malaise Among Patients With Long-...mentioning
confidence: 99%
“…Recent research has found that from 43% to 46% of patients with COVID-19 symptoms meet one or more Myalgia Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) case definitions [18,19,20,21]. Research of ME/CFS might suggest ways to measure Long COVID symptoms.…”
Section: Infectious Diseases Observational Researchmentioning
confidence: 99%
“…In the ME/CFS field, using statistical methods to classify patients has helped identify latent factors [23], and similar methods are beginning to be employed to identify critical domains of COVID-19 and Long COVID symptoms. For example, Guo et al [24] [18] PCA resulted in the following five components: fatigue, post-exertional malaise, daytime sleepiness (lethargy), brain fog, and unrefreshing sleep.…”
Section: Infectious Diseases Observational Researchmentioning
confidence: 99%
See 1 more Smart Citation